Implementasi Program Comprehensive Guidance dalam Pembentukan Karakter Siswa di SMP Muhammadiyah Al Kautsar PK (Program khusus) Kartasura Sukoharjo - M Fadhel Zamhari; Hafidz Hafidz (LP. Ma'arif Janggan Magetan, 2023)
This research reflects an effort to explain the implementation of the Comprehensive Guidance program in shaping students' characters at SMP Muhammadiyah Al Kautsar PK (Special Program) Kartasura Sukoharjo. The purpose of this research is to reveal details about the implementation of the Comprehensive Guidance program in shaping students' characters and to identify factors that support and hinder the implementation of the program in character formation. Data collection methods used involved observation and interviews, while data processing was done using a qualitative approach. This approach was chosen to analyze data derived from observations and interviews. The results of this research indicate that the Comprehensive Guidance Program consists of five types of guidance: academic, health, social, spiritual, and long-live guidance. Supporting factors in the implementation of this program include young, energetic teachers who are enthusiastic about guiding children, as well as support from parents. However, there are some inhibiting factors, such as not all teachers having the skills to guide children and the fact that character formation cannot be achieved in a short period.